Pengaruh Penerapan Pembelajaran Kelompok Heterogen Berbasis Lima Bahasa Kasih terhadap Keterampilan Kolaborasi Siswa di SDN 24 Mataram - Annisa Kurniati (Syntax Idea)
Collaboration skills are one of the most important skills for 21st century students. Collaboration skills are needed in the world of work and social environment. Collaboration skills can be trained in the learning process by implementing heterogeneous group learning. The implementation of heterogeneous groups provides space for students to teach and support each other, but has the potential to reduce student focus in the learning process. Heterogeneous group learning also has challenges, such as determining the right material analysis and learning methods, low participation rates, difficulty cooperating, difficulty sharing ideas, and lack of appreciation for the contributions of other members in the group. These challenges are minimized by using the language of love in the learning process. Recharging the batteries of a loved one with the right love language will foster a sense of security in the loved one. There are five kinds of love language, namely giving positive words (word of affirmation), providing assistance / service (act of service), quality time together (quality time), giving gifts (receiving gifts), and providing physical touch (physical touch). This descriptive qualitative research observation was conducted at SDN 24 Mataram. Using purposive sampling technique, class V was chosen as the subject of observation, considering the heterogeneity of cognitive levels and learning styles of students. After 5 days of implementing heterogeneous group learning based on the five love languages, the results were positive. Group one was categorized as “collaborative” for collaborative attitude and character indicators. Group one was categorized as “highly collaborative” for active collaboration behavior and skills. Group two and group three were categorized as “very collaborative” for all three indicators. These results indicate that grade V students have potential collaboration skills. Group learning based on the five love languages is flexible, can be applied in various learning models.